Costa Rica´s wind resource assessment: A case study for Cartago province - Murillo-Zumbado, Gustavo (2021)
Wind resource assessment is essential for the development and implementation of wind power systems. Costa Rica have no studies by zones in a specific way as proposed, which allows professionals in the area to make decisions based on the potential and characteristics of the wind. This study provides for the first time the characterization of the wind resource in the province of Cartago. The characterization is carried out for the surface boundary layer, with data measured at 10 m above ground level, taking the magnitude of the wind speed and direction obtained from eight meteorological stations. During the characterization of the wind resource, the data was analyzed statistically and using computational codes that allowed obtaining results from the information collected. When processing the information provided by the meteorological stations, it is determined that the average wind speeds are between 3 m/s and 5 m/s at a height of 10 m above the surface. In addition, the intensity of turbulence is recorded between 15% and 30% and two well marked periods were determined in terms of the magnitude of the wind, from November to February for strong intensities and September to October for lower intensities. For the province of Cartago, the directions that predominate are the North or East components, being the two most recurrent components in the analyzed data.